Analisa Sentimen Publik Terkait Otonomi Khusus (OTSUS) di Papua dengan Pendekatan Sains Data - Harun B S O. Mosioi; Evangs Mailoa (Prosiding SISFOTEK, 2021)
This study explores conversations on Twitter related to Otonomi Khusus Papua. Twitter users in Indonesia are fewer compared to the USA, even the minimum number of Twitter users in Papua. However, topics related to Otonomi Khusus Papua are intense on Twitter. The author's hypothesis talks about the Otonomi Khusus Papua are not Papuan people. This is interesting for the author to look further at sentiment analysis related to the topic of Otonomi Khusus Papua (otsus) on Twitter. This research uses a data science approach utilizing machine learning with drone emprit. Data retrieved via Twitter API is filtered, retrieved, and analyzed. The results show that Otonomi Khusus Papua topics contain more positive narratives but users who raise these positive narratives are bots.